Analisis faktor penentu kinerja pegawai Rumah Sakit Umum Daerah Kabupaten Manokwari - Sopia Manusawai; Jacob Manusawai; Anton S. Sinery (Program Pascasarjana Universitas Papua, 2021)
The aims of this research is to study the defining factor of employee performance on RSUD Manokwari, spesifically the impact of leadership, cultural organization, and work motivation to the employee performance. The methods that is used in this research was descriptive methods with interview and obervation. The interview was conducted with the employee of RSUD Manokwari while observing the performance of them. The respondences of this research are 202 people who work in RSUD Manokwari, consisting of ASN staff and the honorary staff. The result shows that leadership take a positive effect on administration staff performance in RSUD Manokwari. Also, the organisation culture and work motivation have a positive impact on the Administration staff in RSUD Manokwari.